(3QSGdI GdMceI GdYQTjI aj EKHGJ GdhGLHs - (3eMeO Hf EHQGgje Hf jMji GdbhGej GdTjQGRj, GdedG UOQGdOjf,J (B1059 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hGdMeO ef fYeg CeG HYO abO SGdfi HYV ef jgefi Cf GPcQ dg QSGdI eTJedI Ydi NUGFU Yde GdJhMjO s
(3BNQgG (B:s
(3Cf GdNjQ ebUhO HGdbUO GdChd hGdMeO ddg hGgH GdYbd s
(3Vef eLehY , JQJjHgG (B: (3GdNGeS hGdKdGKhfs
(3GfXQg eY GdeNWhW Qbe (B292 (3ef faS GdHYKIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B303s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdadSaI hGdefWbs